Development of Experimental Student Worksheets Based on Scientific Approach for Student Grade XI Semester 1 - Indri Kasih; Ristiono Ristiono; Rahmawati Darussyamsu (Bioeducation Journal, 2018)
LKPD Experiment based on Scientific Approach can guide students in developing a concept from the materials they have learned in lab work activity. Based on the matter, a study had done which aimed to produce LKPD experiment using Scientific Approach Based for the students grade XI at SMA/MA it was valid and practical.This study was an elaborated study which had three stages in conducting the research. There was known as 4D model which were define, design, develop. The data were collected by using validity questionnaire and practicality. The subject of this study were 2 biology lecturers, and 2 biology teachersas the validators, 2 biology teachers and 25 students grade XI Science at SMAN 1 Batusangkar, as the practicalitator. The data of this study was primary data which was validity and practical data. The result of this study showed that the LKPDexperiment based on scientific approach for the students grade XI 1st Semester SMA/MA was really valid and really practical.